2017
DOI: 10.1163/15685403-00003653
|View full text |Cite
|
Sign up to set email alerts
|

Size-mediated, density-dependent cannibalism in the signal crayfish Pacifastacus leniusculus (Dana, 1852) (Decapoda, Astacidea), an invasive crayfish in Britain

Abstract: The role of cannibalism in crayfish populations is not well understood, despite being a potentially key density-dependent process underpinning population dynamics. We studied the incidence of cannibalism in an introduced signal crayfish Pacifastacus leniusculus population in a Scottish lowland river in September 2014. Animals were sampled using six different sampling techniques simultaneously, revealing variable densities and size distributions across the site. Cannibalism prevalence was estimated by analysing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
(58 reference statements)
0
27
0
Order By: Relevance
“…As abundance increases, changes in crayfish behaviour to reduce the risk of antagonistic interactions with conspecifics might cause a shift in habitat use or time spent foraging (Svanbäck & Bolnick, ), causing individuals to consume resources at lower trophic levels. However, a recent study suggested that cannibalism in crayfish increases with population density (Houghton et al., ). The negative effect of population abundance on trophic position was only evident in smaller lakes which might be linked to an increase in encounter rates between conspecific individuals, since these are likely to increase in smaller areas if abundance remains the same.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As abundance increases, changes in crayfish behaviour to reduce the risk of antagonistic interactions with conspecifics might cause a shift in habitat use or time spent foraging (Svanbäck & Bolnick, ), causing individuals to consume resources at lower trophic levels. However, a recent study suggested that cannibalism in crayfish increases with population density (Houghton et al., ). The negative effect of population abundance on trophic position was only evident in smaller lakes which might be linked to an increase in encounter rates between conspecific individuals, since these are likely to increase in smaller areas if abundance remains the same.…”
Section: Discussionmentioning
confidence: 99%
“…Our results appear to support the first theory, especially since it was found that individual trophic position also nick, 2007), causing individuals to consume resources at lower trophic levels. However, a recent study suggested that cannibalism in crayfish increases with population density (Houghton et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For population control programmes to be successful, Bomford and O'Brien (1995) suggested a number of criteria have to be met, including that all reproductive animals must be at risk of capture, with their capture still probable at low population density. For invasive crayfish, an issue is the low rates of capture and removal of juveniles (<30 mm carapace length), despite them often comprising a high proportion of population abundance (Houghton et al, 2017). Thus, trapping methods that are biased towards the capture of only mature crayfish tend to result in poor control efficiency due to much of the population remaining unaffected (Peay, 2004).…”
Section: Introductionmentioning
confidence: 99%